Marcha das Margaridas 2023: alimentação, mobilização social e feminismos - Teixeira, Marco Antonio; Galindo, Eryka; Peuker, Birgit; Campos Motta, Renata (Food for justice working paper series, 2025)
This work presents the data collected in the research “Marcha das Margaridas 2023: Food, Social Mobilization, and Feminisms,” conducted from August 15 to 16, 2023, by the Research Group Food for Justice: Power, Politics, and Food Inequalities in a Bioeconomy, based at the Heidelberg University. This research aimed to understand the social composition and perception of people who participated in the Marcha das Margaridas 2023 on the themes of food, social mobilization, and feminisms. The survey revealed a predominantly female participation (85.4%), with a balanced age distribution among adults (about 50%), youth (about 25%), and elderly (about 25%). In racial terms, approximately three-quarters of participants identified as black [negras], with a predominance of brown [pardas] (about 50%) and black [pretas] (almost 30%) ...
Keywords: Graue Literatur